THE BRAZIL-UNITED STATES BILATERAL RELATIONS IN THE DILMA ROUSSEFF ADMINISTRATION, 2011-2014 - Pecequilo, Cristina Soreanu (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
The goal of the article is to present an analysis of Brazil-U.S. relations during Dilma Rousseff's government from 2011 till 2014, by considering the evolution of Brazil´s foreign policy on the 21st century. The political, strategic and economic components, as well as the opportunities and crossroads of these relations, are examined in the regional and global context.